2009
DOI: 10.1055/s-0029-1215192
|View full text |Cite
|
Sign up to set email alerts
|

An evidence-based consensus statement on the role and application of endosonography in clinical practice

Abstract: Consensus was reached for several clinical scenarios for which the impact of EUS findings was supported by a high level of evidence. These included diagnosis and staging of esophageal cancer, differential diagnosis of subepithelial lesions, thickened gastric folds, assessment of peritoneal involvement in patients with gastric cancer, mucosa-associated lymphoid tissue lymphoma, diagnosis of common bile duct/gallbladder stones, diagnosis of chronic pancreatitis, differential diagnosis of a solid mass in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 56 publications
0
11
0
3
Order By: Relevance
“…Optimal treatment of patients with gastric cancer depends on accurately staging the cancer, and is most commonly accomplished through computed tomography (CT). Recently, endoscopic ultrasound (EUS) has been endorsed for the preoperative staging of gastric cancer by several groups, such as the National Comprehensive Cancer Network, the Brazilian Society of Gastrointestinal Endoscopy, and the Scottish Intercollegiate Guidelines Network [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Optimal treatment of patients with gastric cancer depends on accurately staging the cancer, and is most commonly accomplished through computed tomography (CT). Recently, endoscopic ultrasound (EUS) has been endorsed for the preoperative staging of gastric cancer by several groups, such as the National Comprehensive Cancer Network, the Brazilian Society of Gastrointestinal Endoscopy, and the Scottish Intercollegiate Guidelines Network [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…14 It has been shown to impact treatment strategies in a significant proportion of patients with esophageal cancer. 15 An international multicenter study that compared EUS staging of esophageal cancer to CT alone showed that the additional information obtained by EUS changed patient management in one-third of cases with the majority (85%) of these changes being the advocation of nonsurgical and palliative measures due to identification of advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of EBM principles into EUS practice is indicated for an objective evaluation of the technique; it could also reveal certain aspects that warrant further research [60,61]. The present review aimed to appraise EUS literature of the period 2001-2010 in a comprehensive, comparative manner, grading studies according to levels of evidence and highlighting the most thoroughly investigated topics.…”
Section: Discussionmentioning
confidence: 99%